In-situ microscopy in materials research : leading international research in electron and scanning probe microscopies - Gai, Pratibha L., 1948- (Kluwer Academic Publishers, 1997)
This book presents an authoritative account of innovative interdisciplinary in-situ microscopy developments and applications in this rapidly expanding and fascinating field in material and surface sciences and technologies. Direct studies of dynamic materials close to their natural reaction state to obtain fundamental insights into their processes and properties have always been the goal of material scientists including physicists, chemists, ceramicists, heritage conservation scientists and biologists. This has been realized by the extraordinary pioneering developments by internationally renowned scientists from the USA, Japan, Europe and Australia, described in this book. The book fulfills a strong need for an informative account of the different in-situ microscopy methods and will be especially useful both for young scientists, undergraduates and graduates, embarking on research of materials, and practising materials scientists working in areas as diverse as semiconductor science and technology, integrated circuits, ceramics, superconductors, heterogeneous catalysis, biological processes, polymers and cultural heritage conservation, and describes what can happen to live materials as they react. The book contains thirteen chapters covering in-situ developments and applications in environmental-SEM, field emission-SEM, LEEM, reflection EM, UHV-TEM and HVEM, direct atomic-scale probing of gas molecule-solid interactions with environmental-HVEM, atomic level HVEM with very high temperature sample holders, electron diffraction, scanning tunneling microscopy (STM) including for atomic-scale fabrication of surfaces and high temperature UHV-STM, electron holography and Lorentz microscopy.